(untitled) (Open Herald: Periodical of Methodical Research, 2025)
Breast cancer remains the most common malignancy among women worldwide, with increasing prevalence in Iraq. Hormonal imbalances and liver function are closely linked to breast cancer development and progression. This study investigates the levels of sex hormones (estrogen, progesterone, testosterone) and liver enzymes (ALT, AST, ALP, GGT) in Iraqi women diagnosed with breast cancer. The research aims to evaluate the biochemical profiles of patients to identify potential diagnostic or prognostic biomarkers. A cross-sectional study was conducted on 100 Iraqi women aged 25–65 with confirmed breast cancer diagnoses. Blood samples were analyzed using ELISA for hormone levels and standard biochemical assays for liver enzymes. The data were statistically analyzed to explore correlations between these biomarkers and cancer stages or histological types. Preliminary results indicate altered levels of sex hormones and elevated liver enzymes in a significant portion of the sample, with notable variation across cancer stages. These findings support the hypothesis that hormonal and hepatic biomarkers can provide valuable insights into breast cancer status. The study contributes to the limited body of research in the Iraqi context and underscores the need for routine screening of sex hormones and liver enzymes in breast cancer diagnostics. Future work should expand on these findings with larger sample sizes and include genetic and lifestyle factors that may influence hormone and liver function. These results may help improve clinical decision-making and personalized treatment plans for Iraqi breast cancer patients.